If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(4 + -3x) = 2(8x + -9) + 6 (4 * 7 + -3x * 7) = 2(8x + -9) + 6 (28 + -21x) = 2(8x + -9) + 6 Reorder the terms: 28 + -21x = 2(-9 + 8x) + 6 28 + -21x = (-9 * 2 + 8x * 2) + 6 28 + -21x = (-18 + 16x) + 6 Reorder the terms: 28 + -21x = -18 + 6 + 16x Combine like terms: -18 + 6 = -12 28 + -21x = -12 + 16x Solving 28 + -21x = -12 + 16x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-16x' to each side of the equation. 28 + -21x + -16x = -12 + 16x + -16x Combine like terms: -21x + -16x = -37x 28 + -37x = -12 + 16x + -16x Combine like terms: 16x + -16x = 0 28 + -37x = -12 + 0 28 + -37x = -12 Add '-28' to each side of the equation. 28 + -28 + -37x = -12 + -28 Combine like terms: 28 + -28 = 0 0 + -37x = -12 + -28 -37x = -12 + -28 Combine like terms: -12 + -28 = -40 -37x = -40 Divide each side by '-37'. x = 1.081081081 Simplifying x = 1.081081081
| -4-2y=-30 | | 9x^2=-28 | | 3x-18=8x+6 | | 2x^2+56=0 | | (x-2)+(x+2)=252 | | 2x-(5+7x)=4-[x(2x+3)] | | 78=3(5r+1) | | 4r^2+4r-224=0 | | F^2-25=0 | | (4b^2-4b)= | | (x-2)(x+2)=252 | | 2z^2-13z-7=0 | | X^3+300=0 | | 8n^2-20n-72= | | (8x*8x*8x)+1= | | 64x^3-343=0 | | x^2+y^2+2x-4y=20 | | (5k^2-3k)= | | log(5)3-x=2 | | 20x^2+52x+19=0 | | 500=5 | | v^2-36+5v=0 | | 8r^2+26rs+15s^2=20rs+6rs+15s^2 | | (8x-7)(x^2-9x+1)= | | -5y+4(3y-1)=7-5(-9-y) | | Ln(1+5x)=0 | | 2(b-ax)=5x | | 1-3y= | | [2x-9]=3 | | 0.5x^2=0.33x | | 19=w-4 | | 2.5x+4=y |